Cross-resistance to antibiotics of Escherichia coli in the inpatient installation of general regional hospital “X” Bali, Indonesia - Mahaputra, I Putu Yudistira; Sanjaya, Dwi Arymbhi; Meriyani, Herleeyana; Juanita, Rr Asih; Siada, Nyoman Budiartha; Kamalia, Made Gek Adisti; Adrianta, Ketut Agus; Noviani, Lusy (Universitas Ahmad Dahlan, 2025)
Escherichia coli (E. coli) is a critical-priority group of MDR bacteria and its spread can occur in hospital inpatient settings. Several studies showed that antibiotics consumption for inpatients can cause E. coli resistance to other antibiotics called cross-resistance. The aim of this study to determine the cross-resistance in E. coli to antibiotics in the inpatient installation of the regional general hospital